Software to study the speed and acceleration of growing and developing of biological systems in the time (Pro-Vel-Ac). Technical note - García, Yaneilys; Torres, Mildrey; Medina, Yolaine; Gómez, Sarai; Mejías, A. (Cuban Journal of Agricultural Science, 2023)
The design and develop of a software to study the speed and acceleration of growing and developing of biological systems in the time (Pro-Vel-Ac) is showed with the objective of support the researchers performed by the experts in the study of the biological systems evolution. For the implementation of this software, Microsoft Office Excel 2007 was used. The estimation of the speed and acceleration was based on the calculation of the average variation rates. The local maximum and minimum were estimated from the mathematical concepts of the calculation of the critical and inflection points of a function. The software has three sheets: data input, analysis and graphs. It is concluded that Pro-Vel-Ac provides the analysis of data because calculate and illustrate its speed and acceleration without needing a mathematical model. Inform about the estimated time in which the critical points of the growing speed occurs. Also, generate a table that summarizes the characteristics of data, allowing knowing the biological process in study.